Perancangan Ulang Tata Letak Laris Mart dengan Pendekatan Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) - Andya Nabila Arawinda; Muhammad Shafwa; Tifany Claudya Siallagan; Irlina Jilani (JOURNAL SAINS STUDENT RESEARCH, 2024)
Retail trade is experiencing rapid and promising growth among the public, minimarkets are one segment that is growing significantly. This research aims to evaluate the layout of the Laris Mart Store located in Central Bogor District, Indonesia. Data was obtained by interviews and observing facilities in the form of parking, cashier, display room, toilet, employee room, warehouse and ATM. Data analysis uses the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR). Through observation and data analysis, it was found that warehouse placement has a significant impact on employee work efficiency and customer experience. The results of the research data show that the priority room is the cashier because it has the largest TCR value, namely 131. Next, the order of priority level is the warehouse at 120 and the product display rack at 86. These three facilities must be placed close together to allow buying and selling activities and procurement of retail products by the store. will run more optimally and efficiently.